Clonal variation in hybrid aspen wood and bark basic density, heating value and nutrient concentrations - Hytönen, Jyrki; Beuker, Egbert; Viherä-Aarnio, Anneli (Natural Resources Institute Finland, Luke, 2017)
A breeding program with hybrid aspen (Populus tremula x P. tremuloides) was started in Finland during the mid-1990’s. Individual superior hybrid aspen trees were selected and cloned from stands and trials that were left over from an earlier period of hybrid aspen breeding during the 1950’s and 60’s. The main aim of the new program was to produce pulpwood, but hybrid aspen could be grown also as short-rotation crop for bioenergy. Besides growth, also the quality of the crop is an important factor for the user. A series of clone trials including 25 hybrid aspen clones was established in southern Finland in 1998 based on the new selections. To study the clonal differences in wood and bark properties, seven clones at the age of 12 years were selected from one trial. From each clone 5 trees were harvested, and biomass of each tree was measured. Samples were taken for determination of wood and bark basic density, heating value (qv(net)),and nutrient concentrations. We found statistically significant clonal differences in almost all studied properties. The heating value of hybrid aspen was lower than in conifers, but similar with that of some other hardwoods grown in Finland. The study suggests that there are possibilities for selecting nutrient-efficient clones having good growth. Clonal selection based on tree quality characteristics and growth could improve the suitability of hybrid aspen for various end uses.
Keywords: hybrid aspen; clonal forestry; wood density; energy value; nutrients; biomassa